Picture the dead - Griffin, Adele (Naperville, Illinois Sourcebooks Fire, 2010)
After Jennie Lovell's fiancé, Will, is killed during the Civil War, she forms an alliance with a spirit photographer and uses her ability to talk to the dead to investigate the secrets Will was hiding and how he really died.
Php 749.50
Donated by Gorriceta-Rojo family 12.11.18
Keywords: Orphans -- Juvenile fiction; Ghost stories; Love stories; United States -- History -- Civil War, 1861-1865 -- Juvenile fiction